First-principles simulation of electron mean-free-path spectra and thermoelectric properties in silicon. (12th March 2015) - Qiu, Bo; Tian, Zhiting; Vallabhaneni, Ajit; Liao, Bolin; Mendoza, Jonathan M.; Restrepo, Oscar D.; Ruan, Xiulin; Chen, Gang
Abstract: The mean free paths (MFPs) of energy carriers are of critical importance to the nano-engineering of better thermoelectric materials. Despite significant progress in the first-principles–based understanding of the spectral distribution of phonon MFPs in recent years, the spectral distribution of electron MFPs remains unclear. In this work, we compute the energy-dependent electron scatterings and MFPs in silicon from first principles. The electrical conductivity accumulation with respect to electron MFPs is compared to that of the phonon thermal conductivity accumulation to illustrate the quantitative impact of nanostructuring on electron and phonon transport. By combining all electron and phonon transport properties from first principles, we predict the thermoelectric properties of the bulk and nanostructured silicon, and find that silicon with 20 nm nanograins can result in a higher than five times enhancement in their thermoelectric figure of merit as the grain boundaries scatter phonons more significantly than that of electrons due to their disparate MFP distributions.